The Destruction of Legal Reason: Lessons from the Past - Cercel, Cosmin (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The legal predicament of today in Europe and beyond takes the form of a devaluation of the meaning of legality, constitutionality and, of the rule of law. What we are dealing with is yet another crisis of both the tradition of the Rechtsstaat in continental setting and, more broadly, of liberal legality. While this disruption within the sphere of the law seems to mirror the reshuffling in established politics that took place over the last twenty years, it traces back to central jurisprudential questions that have made the substance of crucial debates during the interwar and have fashioned both the field of constitutional theory of the continent and our jurisprudential apparatus for approaching the nexus between law and politics. In this article I argue that the apparent uchronia that the current status of the law opens in relation to past theoretical questions that were seeking to ground legality, is neither a simple by-product of a Zeigeist oversaturated by appeals to procedural democracy or for returns to sovereign power, nor a mere regression to past juridico-political settings. It is a historical development that has been dormant for the past decades, yet has slowly undermined legal thought and praxis. Revisiting, as a matter of historical and jurisprudential inquiry, the context and the content of this original opposition between liberal legality and its enemy, is a way of understanding what constructs our own contemporary situation.